Pharmacognostical Standardization and GC-MS Phytochemical Profiling of Ipomoea quamoclit: An Integrative In-Silico and In-Vitro Study of its Wound Healing Potential (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Ipomoea quamoclit Linn. (Convolvulaceae) is an ethnomedicinal climbing vine traditionally used for the treatment of cuts, burns, and inflammatory skin disorders, yet its wound-healing potential lacks comprehensive scientific validation through standardized pharmacognostic and mechanistic studies. The present investigation was undertaken to evaluate the pharmacognostical characteristics, phytochemical composition, in-silico interactions, and in-vitro wound-healing activity of the ethanolic leaf extract of I. quamoclit. GC–MS profiling identified 194 phytoconstituents, with octadecanoic acid (24.70%) and n-hexadecanoic acid (~25%) as the predominant compounds. Molecular docking of the identified constituents against the inflammatory targets TNF-α and MAPK14 demonstrated that 3-(1-adamantyl)-7-methyl-5-oxo-5h-[1,3]thiazolo[3,2-a]pyridine-8-carboxamide exhibited strong binding affinities (≤−6.8 kcal/mol) and phenol, 4,4'-(1-methylethylidene)bis- exhibited strong binding affinities (≤−8.6 kcal/mol),suggesting significant anti-inflammatory potential. In-vitro evaluation using L929 fibroblast cells confirmed that the extract was non-cytotoxic, maintaining cell viability above 94% in the MTT assay, while the scratch wound-healing assay showed significantly enhanced cell migration and near-complete wound closure at concentrations of 12.5 and 25 μg/mL within 24–36 hours. Collectively, these findings scientifically substantiate the traditional use of I. quamoclit in wound management and highlight its potential as a rich source of biocompatible, pharmacologically active compounds for the development of novel herbal wound-healing therapeutics. Further mechanistic investigations and clinical validation are warranted to establish standardized formulations for future therapeutic applications.
Keywords: Ipomoea quamoclit; insilico; Mtt assay; GC-MS profiling; inflammatory